2017
DOI: 10.1111/bjd.15930
|View full text |Cite
|
Sign up to set email alerts
|

British Association of Dermatologists’ guidelines for the management of pemphigus vulgaris 2017

Abstract: Plain language summary available online

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
262
2
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(298 citation statements)
references
References 287 publications
(411 reference statements)
1
262
2
33
Order By: Relevance
“…The evolution of PV typically begins with painful mucosal ulceration, especially in the mouth . These ulcers are persistent; individual ulcers may come and go but new lesions continue to appear.…”
Section: Diagnostic Cluesmentioning
confidence: 99%
“…The evolution of PV typically begins with painful mucosal ulceration, especially in the mouth . These ulcers are persistent; individual ulcers may come and go but new lesions continue to appear.…”
Section: Diagnostic Cluesmentioning
confidence: 99%
“…According to study on 155 patients on immunosuppressive therapy 94 patients developed secondary infections 9 . Some studies have showed that low-level laser therapy can provide immediate and signifi cant analgesia in patients with pemphigus vulgaris 10 . Systemic corticosteroids are the most useful drugs in the treatment of pemphigus vulgaris and continue to be the mainstay of therapy for this disease.…”
Section: Case-reportmentioning
confidence: 99%
“…Systemic corticosteroids are the most useful drugs in the treatment of pemphigus vulgaris and continue to be the mainstay of therapy for this disease. Their use rapidly induces remission in the majority of patients but the clinician must weigh the benefi ts against the hazard from side effects of the drug 9,10 .…”
Section: Case-reportmentioning
confidence: 99%
“…An effective initial dose of corticosteroids has been suggested to be 1 mg/kg/d [9]. Others recommend an initial oral prednisolone dose of 40-60 mg/d and with severe PV, 60-100 mg/d [10]. A randomized control trial of 20 patients showed that pulsed oral dexamethasone (300 mg/d for 3 days) in addition to oral prednisolone and azathioprine does not improve time to remission, duration of remission or mortality.…”
Section: Systemic Corticosteroidsmentioning
confidence: 99%